2023
DOI: 10.1038/s41416-022-02133-6
|View full text |Cite
|
Sign up to set email alerts
|

A phase I trial of LXS196, a protein kinase C (PKC) inhibitor, for metastatic uveal melanoma

Abstract: Background Up to 50% of patients with uveal melanoma develop metastases (MUM) with a poor prognosis and median overall survival of approximately 1 year. Methods This phase I study evaluated the safety, tolerability, pharmacokinetics, pharmacodynamics and efficacy of the oral protein kinase C inhibitor LXS196 in 68 patients with MUM (NCT02601378). Patients received LXS196 doses ranging from 100–1000 mg once daily (QD; n = 38) and 200–400 mg twice daily (BID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Phosphorylation of PKCδ reflects its ability to autophosphorylate itself, which is required for full enzymatic activity. 19 Single PO dose PK/PD study with LXS196 dosed at 15, 30, 75, and 150 mg/kg demonstrated dose-proportional PK up to 75 mg/kg with strong inhibition of pPKCδ seen across all doses (Figure 5A,B). To understand the antitumor activity of LXS196 in the 92.1 xenograft model, it was then profiled in an efficacy study, where it showed dose-proportional efficacy up to 75 mg/kg bid, achieving regression at the top doses of 75 and 150 mg/kg bid.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Phosphorylation of PKCδ reflects its ability to autophosphorylate itself, which is required for full enzymatic activity. 19 Single PO dose PK/PD study with LXS196 dosed at 15, 30, 75, and 150 mg/kg demonstrated dose-proportional PK up to 75 mg/kg with strong inhibition of pPKCδ seen across all doses (Figure 5A,B). To understand the antitumor activity of LXS196 in the 92.1 xenograft model, it was then profiled in an efficacy study, where it showed dose-proportional efficacy up to 75 mg/kg bid, achieving regression at the top doses of 75 and 150 mg/kg bid.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…The resulting optimized PKC inhibitor, LXS196, demonstrated dose-dependent exposure with rapid and complete absorption across multiple preclinical species and achieved regression in the 92.1 human xenograft in mice. LXS196 is being investigated in the clinic as monotherapy and in combination with other agents for the treatment of MUM …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Darovasertib, a next-generation inhibitor of protein kinase C (PKC), is being clinically developed in both the neoadjuvant and metastatic disease settings. 56 Hepatocyte growth factor (HGF) has been identified in the tumor microenvironment of UM, 57 and elevated HGF levels have been correlated with metastatic UM. 58 Preclinical data indicate that HGF expression is upregulated through the activation of the PKC/MAPK and PI3K/AKT pathways, leading to heightened UM cell proliferation and survival.…”
Section: Management Of Primary Uveal Melanoma Local Therapiesmentioning
confidence: 99%
“…FAK has been described as an integral node of this non-canonical Gαq pathway [ 18 ]. Agents targeting the Gαq canonical signaling pathway, PLCβ–PKC–MAPK, have been shown to have nearly no impact on the overall survival of patients with mUM, as single agents or when combined with chemotherapy [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%